KAJIAN EKONOMI POLITIK RIAU TELEVISI MELALUI PROGRAM DETAK RIAU DALAM MEMENUHI KEBUTUHAN INFORMASI MASYARAKAT RIAU - Kenna Putri Nasution; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Detak Riau an actual news program that raised about the incident in Riau, Pekanbaru and its surroundings especially in Detak Riau program is divided into several program again. In Detak Riau program also featured speakers who are competent in the form of direct talk show, so the audience can interact with the contact person provided. The purpose of this study was to determine how the program Detak Riau, the study of political economy, as well as see the audience's response to the program Detak Riau.This study uses descriptive qualitative theory of political economy media. Data collection techniques used by realities on the ground through observation, interviews, and documentation. Informants in this study amounted to 6 people consisting of Editor in Chief, Field Coordinator, two journalists, PR Pemko Pekanbaru and 4 people in the audience selected based on purposive sampling. As for data validity checking researcher using triangulation techniques. This study aims to determine program Detak Riau as well as the audience's response and to look at the political economy model of the program.The results showed that process of serving program Detak Riau uses the concept POAC this planning, organizing, actuating and controlling in the management of material news. Most of the audience gave a positive response about the information displayed then there is also a negative response on the news that is always discussed about government in general. This relates to the model of political economy in program Detak Riau, namely the commodification, spatialization, and Structuration. So most of the news content displayed is determined by economic interests and the interests of the owner some the political elite. Detak Riau beating of media institutional renewal through horizontal, while the RTV structuration under the auspices of Jawa Pos Group and Riau Pos Group is not so great, because investors or stock investor is not involved in politics.Key word : Detak Riau, Commodification, Spatialization, Structuration